2015
DOI: 10.3310/eme02040
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of Antiglucocorticoid augmentation (metyrapone) of antiDepressants in Depression (ADD Study)

Abstract: BackgroundDepressed patients who do not respond to second-line antidepressant drugs are characterised as suffering from treatment-refractory depression (TRD). Chronic psychosocial stress hypothalamic–pituitary–adrenal (HPA) axis dysfunction is associated with attenuated responses to antidepressants. Corticosteroid co-administration reduces the increase in forebrain 5-hydroxytryptamine with selective serotonin reuptake inhibitors, whereas antiglucocorticoids have the opposite effect. A Cochrane review suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 128 publications
0
4
0
Order By: Relevance
“…The participants with MDD (case group) were recruited as part of the ADD study, which was a clinical trial that aimed to assess the efficacy of metyrapone (a cortisol synthesis inhibitor) as an adjuvant to selective serotonin reuptake inhibitors (SSRIs) in treating MDD in those previously shown not to respond to at least two forms of treatment (treatment-refractory MDD) 12 . Participants were recruited from multiple UK centres, which included Manchester, Leeds, Bradford and Newcastle.…”
Section: Methodsmentioning
confidence: 99%
“…The participants with MDD (case group) were recruited as part of the ADD study, which was a clinical trial that aimed to assess the efficacy of metyrapone (a cortisol synthesis inhibitor) as an adjuvant to selective serotonin reuptake inhibitors (SSRIs) in treating MDD in those previously shown not to respond to at least two forms of treatment (treatment-refractory MDD) 12 . Participants were recruited from multiple UK centres, which included Manchester, Leeds, Bradford and Newcastle.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that interventions to address these systemic affects should help to slow the onset and intensity of depression. Indeed, recent efforts have explored the antidepressant effects of cortisol synthesis inhibitors [226,227] and anti-inflammatory medications [228][229][230] in depression. Greater aerobic physical activity may also help prevent the occurrence of chronic aberrant allostatic predictions, which is consistent with findings that those who are physically active have a prospectively lower risk for depression [231].…”
Section: Implications For Treatmentmentioning
confidence: 99%
“…As expected, the dose of metyrapone needed to suppress physiological cortisol levels was much lower in the evening (500 mg) than in the morning (3 g). Pharmacological suppression of cortisol levels or action has also been explored in a variety of pathological conditions including patients with Cushing’s disease in whom hypercortisolism could not be controlled by a surgical intervention ( 392 , 393 ), and more recently in patients with treatment-refractory depression ( 394 ) or type 2 diabetes ( 395 ). A recently published multicenter retrospective study assessed the effectiveness of metyrapone in controlling cortisol excess in a large series of patients with Cushing’s syndrome and concluded that metyrapone is an effective therapy for short- and long-term control of hypercortisolemia ( 396 ).…”
Section: Manipulating the 24-hour Rhythm Of Circulating Glucocormentioning
confidence: 99%